Stereoscopic video display enhancement - Zhu, Jiang. (2010)
An s3d video file consists of a series of 3D images with 2D-plus-depth format. Each image is obtained from the video and processed separately, and finally combined together to form an enhanced 3D video. To enhance the 3D effect of each image, there are three proposed methods. The first one is „linear method‟. The pixel value in the original depth image is to be added (subtracted) or multiplied (divided) by a constant value, so that all objects in the image will get closer or leave further away from observer as a whole. The second method is „nonlinear method - histogram stretch‟. In this method, the histogram of the depth image is to be stretched as much as possible. There are two ways to reach this purpose, one is histogram equalization and the other is using stretchlim function in matlab. The third method is „s-curve method‟. With this method, a certain threshold value is set at the beginning. Adjustment is applied to the pixel value in the depth image so that if value is less than the threshold value, it will become smaller; if value is greater than the threshold value, it will become larger. This is aimed to bring those objects in front of the screen closer to observer and push those objects at the background further away. This method will also enhance the 3D effect significantly. The 3D effect of a stereoscopic video can be enhanced as a whole, or an object of interest can be picked up and processed separately. In this report, an approach to select out a single object based on region growing in the depth image is proposed. The object in the next frame of a video can be selected out based on the object in the previous frame. So for a period of video with the same scene, the object of interest only needs to be select out in the first frame, and it will be found automatically in the following frames.